Effects of synthesized curcumin derivatives (MS65) on interleukin-6 and its signalling pathways in histamine-induced keratinocytes cell line - Razali, Nurul Atika (2017)
Allergic skin diseases are the most common dermatological problems with a dramatic increase in prevalence over the last few decades. Histamine is a well-known chemical mediator that is involved in allergic inflammation and immune modulation by regulating numerous cellular functions via up-regulation of proinflammatory cytokines. In recent years, antihistamines remain the mainstay of allergy treatment by suppressing the transcription of inflammatory cytokines, chemokines and adhesion molecules. However, current usage of antihistamines is limited in efficacy and associated with several common side effects. Currently, alternative therapeutic preferences are derived from natural products in an effort to provide safer and more reliable anti-inflammatory agents. Chalcone, curcumin and their derivatives are among compounds of interest in natural product research due to numerous pharmacological benefits including anti-inflammatory activities. Therefore, the aim of this study was to investigate the effects of synthesized compounds consisting of chalcone and curcumin derivatives in reducing cytokine production in human keratinocytes upon stimulation with histamine, a potent mediator of allergic responses. In the present study, IL-1β and IL-6 cytokine production in histamine-induced human keratinocytes cell line (HaCaT) were measured using ELISA and cytotoxicity effects were determined using MTT assay. Histamine (10 μM) enhances the production of IL-1β and IL-6 in HaCaT cells, with the highest production of IL-1β and IL-6 at 2.67 ± 0.43 pg/mL and 97.41 ± 2.33 pg/mL respectively after 24 h of exposure. Four chemically synthesized compounds consisting of chalcone derivatives (FLA and FLB) and curcumin derivatives (BDMC33 and MS65) were then evaluated for their inhibitory effects on IL-6 production in histamine-induced HaCaT cells. Out of the four compounds tested, the curcumin derivative (MS65) demonstrated a promising anti-inflammatory activity by inhibiting IL-6 production with IC50 value of 4.91 ± 2.50 μM with low cytotoxicity effect to HaCaT cell and LC50 value of 28.82 ± 7.56 μM. MS65 has shown to inhibit IL-6 through NF-κB and MAPK pathways by suppressing H1R, PKC, IKK-α, IκB-β, NF-κB, c-Raf, MEK and ERK genes. MS65 showed the highest inhibition on H1R gene by 5-fold (0.23 ± 0.02 fold expression) at the concentration of 6.25 μM. The present study has provided mechanistic insights into the ability of MS65 to reduce inflammatory cytokine production stimulated by histamine in human keratinocytes via inhibition of NF-κB and MAPK pathways. These findings suggest that the curcumin derivative, MS65 could be used as a lead compound on developing new medicinal agent for the treatment of allergic skin diseases.